Equilibrium solubility study to determine fexofenadine hydrochloride BCS class and challenges in establishing conditions for dissolution profiles applied to suspension - Lorena de Sousa Rosa; Flávia Dias Marques-Marinho; Silmara Leôncio Braga; Jacqueline de Souza (Universidade de São Paulo, 2020)
The aim of this work was to perform solubility studies for fexofenadine hydrochloride and establish dissolution conditions for this drug in oral suspension dosage form. The solubility study was executed through the shake-flask method, below 37 ºC±1 ºC, at 100 rpm stirring for 12 h in three buffer solutions: hydrochloric acid pH 2.0, acetate pH 4.5 and phosphate pH 6.8. The dissolution test was developed in vessels containing 900 mL of the same buffer, employing the paddle apparatus in speed of 25 and 50 rpm, below 37 ºC±0.5 ºC. The drug was classified as low solubility according to the Biopharmaceutics Classification System, since the dose/solubility ratio was higher than 250 mL in all media tested (326.55 mL in buffer pH 2.0; 2,456.33 mL in buffer pH 4.5 and 1,021.16 mL in buffer pH 6.8). The dissolution test showed that a release of 85% in 30 min could be established. The rotation speed of 25 rpm, media volume of 900 mL and insertion of the samples through weighted syringes are adequate. The buffered media pH 2.0 could be chosen as dissolution media.